PEMERAMAN UNTUK MENINGKATKAN KUALITAS KEJU YANG DIINOKULASI Rhizopus oryzae SEBAGAI SALAH SATU SUMBER BELAJAR BIOLOGI - Estikomah, Solikah Ana (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
Cheese is dairy product resulted from fermented mild in which the fermentation process can be done by lactid acid bacteria or fungus. R.oryzae is able to produce lactic acid, protease and lipase. Ripening process changes the taste and texture. The purpose of this research is ripening to improve the quality of inoculated cheese Rhizopus oryzae. This research the ripening was conducted the concentration variation of temperature (5oC; 10 oC; 15oC), and time (7 days; 14 days). The procedure of research consisted of two steps. The first was un-ripened cheese preparation. The second was the ripening cheese preparation. Cheese produced in this study analyzed the value of pH, fat content, protein content, amino acid levels and identification of microba with Anava then followed by DMRT at 5% level of significance. Data results were analyzed with the likes nonparametric statistical test, followed by Fridman Wilcoxon Signed Rank Test (WSRT) at 5% level sigifican.The results showed that the preferred ripened cheese panelist at a temperature of 150C for 14 days has a pH value of 4.40, the highest protein content of 9.78%, and fat content of 35.02%. Differences affect ripening conditions of pH, fat content, protein content and do not affect the levels of amino acids that formed ripened cheese. The results of identified microba in un-ripened cheese and ripened cheese include Enterococcus hirae (Enterococcus faecalis), Bacillus subtilis, and Aspergillus sp. Kata kunci: Keju, fermentasi, Rhizopus oryzae, pemeraman, suhu.